The Influence Of Influencer Marketing, Fomo, And Brand Image On Impulsive Buying Of Timephoria On Tiktok - Kharisma Ratu Rania; Ahmad Jaenudin (Economics and Digital Business Review, 2026)
The present inquiry assesses whether Influencer Marketing, Fear of Missing Out (FOMO), and Brand Image account for Impulsive Buying of Timephoria cosmetics through TikTok among female undergraduates at Universitas Negeri Semarang. A quantitative design was applied to responses from 106 participants selected through criterion-based sampling. Eligibility required enrollment in the 2023 cohort, regular TikTok use, prior exposure to Timephoria-related posts, and at least one purchase of the brand through the application. Information was obtained with a questionnaire offering five Likert response options and processed through multiple linear regression in IBM SPSS Statistics 26. The estimates show that Influencer Marketing and FOMO each contribute positively and meaningfully to Impulsive Buying, while Brand Image does not provide a statistically supported independent contribution. Influencer Marketing yields the largest standardized coefficient (β = 0.320). These outcomes imply that immediate cosmetic transactions on TikTok arise from both persuasive promotional exposure and consumers' emotional concern about falling behind current trends. The inquiry broadens discussion of purchasing conduct within social-commerce environments and offers practical direction for cosmetic firms seeking to design more effective promotional communication on short-video platforms.